Analisis Kepuasan Nasabah Terhadap Pelayanan Jasa Perbankan Secara On Line Melalui Ponsel (Mobile Banking M-BCA) pada PT. BCA Tbk. KCP Cibubur - Yustiana Wardhani; Vevi Firmayanti (STIE Binaniaga, 2009)
Increasing number of banks in Indonesia and the increased facilities owned by each bank, making the level of competition among banks is also increasingly fierce. Any banks compete to provida services and the best service for the community. Strategis in the travel by the banks, among others, improve the quality of the product or service and convenience in transaction facilities. Bank Central Asia (BCA) as one of the banks in Indonesia, of course must be responsive in the face of such competition. In this case trying to get products and services are more specific in order to provide maximum satisfaction to its customers and also attract a wider consumer, so that excel in competition, because customer satisfaction is not only derived from the product features alone but must be a combination of features and quality service provided. Based on the analysis of IPA which is a mapping of each attribute of service into the cartesian diagram Attributes that are in quadrant I or high priority are (1) Speed of service m-BCA m-payment transactions (credit card payments, electricity, telephone, etc.), (2) Speed of service m-BCA conduct m-commerce transactions (purchase refill pulse), (3) Speed of service m-BCA in providing information, (4) Ease of service m-BCA m-payment transactions (credit card payments, electricity, telephone, etc.), and (5) Ease of service m-BCA m-commerce transactions (purchase refill pulse). Attributes that are quadrant II or maintain performance are (1) Speed of service m-BCA in conducting transactions m-info (&mutations account balance), (2) Speed of service m-BCA in the m-transfer transactions (inter BCA & inter-Bank), (3) Ease of service m-BCA in conducting transactions m-info (& mutations account balance), (4) Ease of service m-m-BCA transfer transactions (inter BCA & inter-bak), (5) Security uses m-BCA in financial transactions, and (6) Security using m-BCA in non-financial. transactions. Attributes that are in quadrant III or low priority are (1) The ability of providing the promised services, and (2) m-BCA service instructions, and attributes that are at or excessive quadrant IV are (1) Display service menu m-BCA easily understood, (2) tidiness on screen service menu m-BCA, (3) Speed of service m-BCA in conducting transactions m-admin (activation of m-BCA, change PIN), and (4) Ease of service m-BCA in conducting transactions m-admin (activation 0f m-BCA, change PIN).